The Functional Properties of Rabbit Skin Gelatin Compared to Commercial Gelatin and Its Application in Jelly Candy - Nurwantoro Nurwantoro; Antonius Hintono; Anang Mohammad Legowo; Sri Mulyani; Tisqa Rizky Quna; Sutaryo Sutaryo (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2022)
Rabbit skin can be utilized as an ingredient in gelatin making. Gelatin can be used in jelly candy. The study aims to compare the functional properties of rabbit skin gelatin and commercial gelatin in gel strength, viscosity, and ash content and to determine the different test and hedonic test of jelly candy. This study used the t-test with 2 treatments and 8 replications. The rabbit skin gelatin was prepared using hydrochloric acid solution. The commercial gelatin is gelatin from cowhide (Gelita bronze gelatin). The results showed that P1 (rabbit skin gelatin) and P2 (commercial gelatin) were not different on gel strength, however, there was a difference on viscosity and ash content. The difference test on jelly candy state that there was a significant difference between rabbit skin gelatin jelly candy and commercial gelatin jelly candy. The hedonic test on jelly candy gave no difference on texture, flavor, taste, and overall, except there was a difference on color. The color of jelly candy with rabbit skin gelatin is a cloudy white, while jelly candy with commercial gelatin is a clear white. Both jelly candies can be distinguished and accepted by the panelist.